Moral distress interventions: An integrative literature review. (May 2022) - Amos, Vanessa K; Epstein, Elizabeth
Moral distress has been well reviewed in the literature with established deleterious side effects for all healthcare professionals, including nurses, physicians, and others. Yet, little is known about the quality and effectiveness of interventions directed to address moral distress. The aim of this integrative review is to analyze published intervention studies to determine their efficacy and applicability across hospital settings. Of the initial 1373 articles discovered in October 2020, 18 were appraised as relevant, with 1 study added by hand search and 2 after a repeated search was completed in January and then in May of 2021, for a total of 22 reviewed articles. This review revealed data mostly from nurses, with some studies making efforts to include other healthcare professions who have experienced moral distress. Education-based interventions showed the most success, though many reported limited power and few revealed statistically lowered moral distress post intervention. This may point to the difficulty in adequately addressing moral distress in real time without adequate support systems. Ultimately, these studies suggest potential frameworks which, when bolstered by organization-wide support, may aid in moral distress interventions making a measurable impact.